Contract Management and Health Service Delivery in Uganda: A Case Study of Kabale Regional Referral Hospital, Kabale Municipality. - Atwesigire, Banard (Kabale University, 2023)
In the study, the Kabale Regional Referral Hospital was used to demonstrate how contracts were managed and health services were delivered in Uganda. Contract administration, relationship management, and contract closing do in fact have a connection to service delivery (Alinaitwe, 2007; Soliman, 2011; and Young, 2008). The extents of these associations, with a focus on the provision of health services, have not been established in the numerous studies the researcher has evaluated. This created a need for study to be done to determine how contract management relates to the provision of health services in Kabale Municipality. The main objective of the study was to determine the relationship between contract risk management and health service delivery at Kabale Regional Referral Hospital, Kabale Municipality. Additional objectives included assessing the impact of contract planning and contract supervision on health service delivery at Kabale Regional Referral Hospital, Kabale Municipality. In order to investigate the connection between contract management and the delivery of health services in Uganda, this study used a cross-sectional research approach. The study used both quantitative and qualitative methods in a cross-sectional research design. The study included 133 respondents in its sample size. Results for the study's first goal revealed a substantial positive correlation between contract supervision and the provision of health services, with a correlation coefficient of 0.462** and a P-value of 0.000, which was less significant than the 0.01 level of significance. Secondly, the study indicated that contract planning and the provision of health services are positively and significantly related, with a correlation coefficient of 0.428** and a P-value of 0.000, which was below the 0.05 level of significance. A P-value of 0.000 (below the 0.05 level of significance) and a correlation coefficient of 0.793** for objective three's findings on health service delivery, respectively, indicate that there is a strong positive relationship between the two. In a bid to reduce the rising cost of public administration and to remove any discrepancies or overlaps between hospitals and LGs, the study recommended that the Ministry of Health fully administratively decentralizes contract supervision activities to trusted administrators as a matter of policy. It was concluded that there is a positive significant relationship between contract supervision and the delivery of healthcare services at Kabale Regional Referral Hospital in Kabale Municipality, rejecting null hypothesis one, which held that there is no significant relationship between contract supervision and the delivery of healthcare services in Kabale Municipality, there was a positive significant relationship between contract planning and the provision of health services in Kabale Municipality, and there was a positive significant relationship between contract risk management and health service delivery in Kabale Municipality. The study also recommended that, if Kabale Regional Referral Hospital's health service delivery is to be enhanced, ongoing emphasis on contracts risk management be given a priority. The study will help to develop suitable rules and by-laws for better service delivery, where by the “Local Government representatives and other policymakers will receive information regarding contract management.